Appreciative Inquiry Coaching untuk Menurunkan Stres Kerja - Agung Suprapto Dwi Cahyono; Koentjoro Koentjoro (Faculty of Psychology, Universitas Gadjah Mada, 2015)
Many factors such as individual, social, environment, organization and work characteristic factors potentially raising stress. The aim of this study was to examine the impact of appreciative inquiry coaching to reduce work stress of Traffic Policeman. The subjects of this study were Traffic Policeman at Yogyakarta. Experiment design was referred pretest-posttest control group design. Subject divided into two groups, experimental group and control group. The experimental group was the one who received appreciative inquiry coaching as treatment and waiting list for control group. The effectiveness of coaching measured by Traffic Policeman Work Stress Scale that have been given for two groups of this study 3 weeks after and before treatment. By using mixed-anova, the result indicated that Appreciative Inquiry Coaching reduced work stress of Traffic Policeman significantly (F=179.192, p<0.01).